Flycodes enable simultaneous preclinical analysis for dozens of antibodies in single cassette–dosed mice - Justin D. Walter; Michal Beffinger; Pascal Egloff; Iwan Zimmermann; Lea M. Hurlimann; Fabian Ackle; Matthias Seifert; Sebastian Kobold; Johannes vom Berg; Markus A. Seeger (Proceedings of the National Academy of Sciences, 2025)
Protein therapeutics such as antibodies require in-depth in vivo characterization during development and consequently account for a large proportion of laboratory animal consumption in the pharmaceutical industry. Currently, antibody candidates are exhaustively tested one-by-one in animal models to determine pharmacokinetic and pharmacodynamic (PK/PD) profiles. The simultaneous analysis of antibody mixtures in single animals, called cassette-dosing, could in principle overcome this bottleneck, but is currently limited to small cassette sizes. Here, we demonstrate how the use of genetically encoded peptide tags (flycodes), designed for maximal detectability in liquid chromatography-mass spectrometry, can allow for the simultaneous characterization of large pools of drug candidates, from single cassette–dosed mice. We demonstrate the simultaneous assessment of PK parameters for a group of >20 marketed/development-stage antibodies. Biodistribution experiments in mice bearing EGFR-expressing tumors correctly identified the two pool members recognizing EGFR, while organ analysis registered liver accumulation of an antibody targeting glucagon receptor, a protein profoundly expressed in that organ. In analogy to an early-phase drug development campaign, we performed biophysical and PK analysis for a cassette of 80 unique bispecific DARPin-sybody molecules. The data shown in this study originate from only 18 cassette-dosed mice, thereby demonstrating how flycode technology efficiently advances preclinical discovery pipelines allowing a direct comparison of drug candidates under identical experimental conditions.